Design of Alternative Energy Using Thermoelectricity by Utilizing a Dispenser Heat Tank Using IOT - Pratama, Legenda Prameswono; Wilyanti, Sinka; Setiawan, Adi; Hamzah, Hamzah; Manfaluthy, Mauludi; Arief, Yanuar Zulardiansyah; Al-Humairi, Safaa Najah Saud (Eksergi, 2024)
Energy is an object that can move through essentialreactions; increasing population growth is one of the factors forincreasing energy needs. One of the initiatives initiated was thecreation of a Thermal Electric Generator (TEG). The formulationof the problem in this study is to determine the output voltage,current, and power generated by the thermoelectric as analternative energy and to determine the effect of temperature onthe thermoelectric. The goal is to determine the amount of outputthe thermoelectric generates when it gets a heat source from thedispenser. The data source in this study was obtained from testingthe tools made. The test results show the effect of temperature onthe thermoelectric tested for 120th minutes test of max 5.96 Voltswith a water temperature in the dispenser tank of 73C withoutusing a step up using six pieces of thermoelectric arranged inseries.